The formation and development of the relations between Kazakhstan and Japan - Sadykova, R. O. (Journal of Oriental Studies, 2016)
This article is devoted to the mutual relations between Japan and Kazakhstan. The relations of Kazakhstan and Japan from thebeginning of 90’s years were considered on this article. The author paid attention to the conceptual basis as “speech of R. Hashimoto”and agreements signed between Japan and Kazakhstan. Also there were considered the main information on development of tradeeconomic,political and cultural relations between Kazakhstan and Japan.